The problem of revealing political reality in Osip and Nadezhda Mandelshtam’s documents concerning M. Volfson, V. Narbut, N. Bukharin - Leonid Katsis (Литературный факт, 2020)
The work is devoted to the analysis of Osip Mandelstam’s articles “Streams of hackwork (khaltura)” and “On translations” in the broad literary and political context of the 1920 – 1930s. The author suggests comparing these articles with the work and publications of the head of the conscientious political censorship Miron Volfson (1880 – 1932), a member of the board and editor-in-chief of the Gosizdat (State Publishing House), whose name appears several times in Mandelstam’s letters. Analysis of official contacts that Mandelstam had with the leadership of conscientious ideological bodies and highest Soviet ideological authorities, allows us to shed a new light on the origin and meaning of the Mandelstam’s anti-Stalinist “epigram” “We live without feeling the country...” In particular, the author reveals a direct reference to Mandelstam’s article “Streams of hackwork” in Wolfson’s 1929 book “The Ways of the Soviet Book”, where the author, on one hand, sums up the NEP period of the Soviet book publishing history, and on the other, sets the task of a new total centralization of book publishing as an important section of the ideological front. The study allows to put the poet’s articles “Streams of hackwork” and “On translations”, which at first glance are devoted exclusively to the problem of translation, in political context of the second half of the 1920s and early 1930s. The observations and conclusions based of the analysis give the opportunity to substantially correct the information about this period of Mandelstam’s biography, which is contained in the memoirs of his widow N.Ya. Mandelstam.